2023
DOI: 10.3390/vaccines11111633
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Cancer Immunotherapy with a Focus on FDA-Approved Vaccines and Neoantigen-Based Vaccines

Anna Hargrave,
Abu Salim Mustafa,
Asma Hanif
et al.

Abstract: Cancer immunotherapies refer to the concept of retraining the immune system to target malignant cells. Multiple immunotherapeutic options exist including immune modulating antibodies, immune stimulating cytokines, chimeric antigen receptor T cell therapy, and vaccines. Overall, this field has advanced rapidly as knowledge of the tumor microenvironment, immunological pathways, and biotechnology expands. Specifically, advancements in neoantigen identification, characterization, and formulation into a vaccine sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…Despite comprehensive research, however, only a few vaccines have made it into oncology to date: (i) two prophylactic vaccines against HPV and the hepatitis B virus, preventing the development of virus-associated cervical cancer and hepatocellular carcinoma, respectively [21,22]; and (ii) three FDA-approved therapeutic vaccines, i.e., bacillus Calmette-Guerin vaccine for treatment of non-muscle-invasive bladder cancer, Sipuleucel-T (the only FDA-approved autologous cellular immunotherapy for metastatic castrationresistant prostate cancer), and talimogene laherparepvec "Imlygic ® ", an oncolytic viral drug for treatment of advanced melanoma [16,17,23]. To date, melanoma represents the only cutaneous malignancy for which significant research in the field of vaccinology has been conducted [16,[18][19][20].…”
Section: Vaccine Principles In Oncologymentioning
confidence: 99%
“…Despite comprehensive research, however, only a few vaccines have made it into oncology to date: (i) two prophylactic vaccines against HPV and the hepatitis B virus, preventing the development of virus-associated cervical cancer and hepatocellular carcinoma, respectively [21,22]; and (ii) three FDA-approved therapeutic vaccines, i.e., bacillus Calmette-Guerin vaccine for treatment of non-muscle-invasive bladder cancer, Sipuleucel-T (the only FDA-approved autologous cellular immunotherapy for metastatic castrationresistant prostate cancer), and talimogene laherparepvec "Imlygic ® ", an oncolytic viral drug for treatment of advanced melanoma [16,17,23]. To date, melanoma represents the only cutaneous malignancy for which significant research in the field of vaccinology has been conducted [16,[18][19][20].…”
Section: Vaccine Principles In Oncologymentioning
confidence: 99%
“…Recently, studies have been carried out on vaccines against neoantigens in GBM patients. The first phase of a clinical trial showed that vaccination of newly diagnosed glioblastomas with a personalized neoantigen vaccine (NeoVax) induced neoantigen-specific circulating CD4+ and CD8+ T-cell responses and neoantigen specific intratumoral T-cell infiltration (NCT02287428) [ 48 , 49 ]. However, an immune response was not observed in patients who received concomitant dexamethasone-based steroid therapy [ 48 ].…”
Section: Vaccine Therapymentioning
confidence: 99%
“…[5][6][7][8] Furthermore, the development of cancer vaccines has also been considered to be a major challenge in cancer immunology to prevent and fight against cancer. [9][10][11][12][13] In order to obtain a potential therapeutic cancer antigen from thousands of immunopeptide sequences, previous research has relied on a prediction system which usually provides dozens to hundreds of candidate sequences for further screening steps. The presentation machinery of class I immunopeptides is highly complex, involving genetic alteration, source translation, and the cancer microenvironment (Figure 2).…”
mentioning
confidence: 99%